Application of Internet of Things in academic buildings for space use efficiency using occupancy and booking data. (December 2020) - Azizi, Shoaib; Nair, Gireesh; Rabiee, Ramtin; Olofsson, Thomas
Abstract: Environmental sustainability in academic buildings can be improved with management interventions such as improving space use efficiency supported by large data from the Internet of Things (IoT). Due to the potentials, the interest in the use of IoT tools for facility management is high among universities. However, empirical studies on this topic are scarce. To address the knowledge gap in this area, this study proposes and examines a process model with steps to measure space use and to improve space use efficiency by IoT tools in academic buildings. The applicability of the model is investigated in 8 lecture halls in a university building by using occupancy and booking data from IoT tools. Four space use indicators are developed to visualize the data and quantify space use, and based on them, the strategies and interventions for space use efficiency are proposed and discussed. Highlights: Space use efficiency associates with multiple benefits which can lead to environmental sustainability. The large data generated by IoT tools enables facility managers to enhance space use management in buildings. The proposed space use indicators quantify different aspects of space use and can reveal the efficiency gaps. This paper links the management and technical aspects of using IoT tools for improving the efficiency of space use.